Farmer-recognized indigenous rice landraces and community conservation in the Ifugao Rice Terraces, Philippines - MARISSA P. BULONG (Society for Indonesian Biodiversity, 2026)
Abstract. Bulong MP. 2026. Farmer-recognized indigenous rice landraces and community conservation in the Ifugao Rice Terraces, Philippines. Biodiversitas 27 (7): d270712. https://doi.org/10.13057/biodiv/d270712. The Ifugao Rice Terraces in Philippines are a world-renowned agricultural heritage site maintained by indigenous wisdom, communal effort, and traditional rice cultivation methods. Nonetheless, environmental degradation and social transformations increasingly jeopardize the sustainability of terrace agriculture. This project investigated socio-ecological problems impacting rice terrace communities in Nagacadan, Batad, and Bangaan, Ifugao Province, Philippines, and delineated community-based conservation objectives for landscape sustainability. Data were collected from 114 active rice farmers using structured surveys and open-ended interviews. Quantitative data were analyzed using descriptive statistics, while qualitative responses were examined through thematic analysis. Indigenous rice landraces, acknowledged by farmers, were recorded with farmer-reported local names and community validation instead of morphological or genetic characterization. The research identified 27 indigenous rice landraces acknowledged by farmers, cultivated in three villages, and documented the ongoing use of traditional ecological knowledge about rice farming, irrigation management, terrace upkeep, and postharvest processing. Terrace erosion, water scarcity, declining irrigation systems, labor shortages, insufficient capital, youth disengagement, and terrace neglect were identified as the predominant socio-ecological issues. Farmers recognized terrace rehabilitation, irrigation restoration, agricultural machinery support, financial aid, and postharvest enhancement as the most commonly prioritized conservation measures. These findings offer pragmatic recommendations for enhancing farmer-led conservation measures that promote the enduring sustainability of farmer-acknowledged indigenous rice landraces and agricultural heritage landscapes in the Ifugao Rice Terraces.